Comparative analysis of optimism and life satisfaction in Brazilian male and female Ju-Jitsu society - Wojdat, Marta; Kanupriya, Rawat; Janowska, Patrycja; Wolska, Beata; Stępniak, Robert; Adam, Marek (Journal of Education, Health and Sport, 2017)
Aim: The comparision of the level of optimism and life satisfaction of men and women in the Brazilian ju-jitsu population, based on the average result of these characteristics of Polish society. Material and Methods: The group of 63 former and current paricipants being in training was exemined in Brsilian Ju-Jitsu (27 women and 36 men) and 76 being out of training participants from the minitoring group (38 women and 38 men) using the SWLS (Satisfaction with Life Scale) test to define the level of life satisfaction and the LOT-R (Life Orientation Test Revised) test to define the level of optimism. Results: There were significant differences in the level of optimism and life satisfaction among BJJ participants and those who did not practice any physical activity. The different responses of BJJ training to the "psyche" of men and women were also revealed as well as the little influence of sociological factors. Conclusions: The Brazilian Ju-Jitsu training significantly improves mental well-bing of a person. The sociological factors seem to have a minor effect on the state of "psyche" of BJJ paricipants.